PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM PEMBELAJARAN IPS SISWA KELAS V SDN 1 ALAS - Azmi Qurnaini; Nurhasanah; Iva Nurmawanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem-solving ability of class V students at SDN 1 Alas is still low, because out of 27 there are 9 students who cannot be seen from the unsatisfactory grades obtained. This is because the teacher uses the lecture method so that the teacher is more dominant than the students. This research aims to determine the effect of the problem-based learning model on problem-solving abilities in social studies learning for class V students at SDN 1 Alas. This type of research uses quantitative research with the quasi-experimental design method, the nonequivalent control group design type. Data collection methods include observation sheets and tests. Based on the research results of independent sample t test hypothesis testing, it was obtained that t count (8.320) > t table (2.006) and the effect size obtained was 2.265, which is in the range of values > 2.0, which proves that there is a significant influence between problem solving abilities in the class. The experiment used the Problem-Based Learning learning model compared to the control class, which used conventional methods (lectures).